2015
DOI: 10.1002/hrm.21705
|View full text |Cite
|
Sign up to set email alerts
|

Ambidexterity and Unit Performance: Intellectual Capital Antecedents and Cross‐Level Moderating Effects of Human Resource Practices

Abstract: International audienceThis study develops a cross-level model examining the effects of intellectual capital facets (i.e., human, social, and organizational capital) on unit ambidexterity. Further, it proposes that organizational-level high-performance human resource (HPHR) practices significantly shape these effects as well as the unit ambidexterity–unit performance relationship. Hierarchical linear modeling on multisource and lagged data from a sample of 148 business units from 58 US Fortune 500 firms shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(126 citation statements)
references
References 97 publications
(171 reference statements)
8
104
1
Order By: Relevance
“…Most studies have focused their attention on the organizational level, examining factors that can drive and leverage the ability of an organization to achieve ambidexterity and through it enhance organizational performance (for a review see Raisch & Birkinshaw, 2008). Realizing that ambidexterity can occur at different levels within the organization, parallel to these studies, other research has shifted its attention to the unit (e.g., Chang, 2015;Kostopoulos et al, 2015) Further expanding extant research on ambidexterity, this study responds to recent calls for research on ambidexterity from a micro-foundational lens and specifically on the constructive and disruptive roles of power and politics in social relationships (Ahammad et al, 2015;Junni et al, 2015) by investigating the role of influence dynamics and political skill on task performance. To shed more light on the efficacy of managers to get their job done, we first examined whether the joint use of two antipodal influence tactics (hard and soft), which we coined influence tactic ambidexterity, can increase their task performance as assessed by their supervisors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have focused their attention on the organizational level, examining factors that can drive and leverage the ability of an organization to achieve ambidexterity and through it enhance organizational performance (for a review see Raisch & Birkinshaw, 2008). Realizing that ambidexterity can occur at different levels within the organization, parallel to these studies, other research has shifted its attention to the unit (e.g., Chang, 2015;Kostopoulos et al, 2015) Further expanding extant research on ambidexterity, this study responds to recent calls for research on ambidexterity from a micro-foundational lens and specifically on the constructive and disruptive roles of power and politics in social relationships (Ahammad et al, 2015;Junni et al, 2015) by investigating the role of influence dynamics and political skill on task performance. To shed more light on the efficacy of managers to get their job done, we first examined whether the joint use of two antipodal influence tactics (hard and soft), which we coined influence tactic ambidexterity, can increase their task performance as assessed by their supervisors.…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of available empirical work on organizational ambidexterity has been carried out at the firm or business unit level and there is a relative shortage of studies at the individual level (Junni et al, 2013;Turner et al, 2013). Previous studies on organizational ambidexterity have been mostly concerned with identifying its antecedents (e.g., Cegarra-Navarro & Dewhurst, 2007;Heavey, Simsek, & Fox, 2015) or its consequences for unit (e.g., Kostopoulos, Bozionelos, & Syrigos, 2015) or firm performance (e.g., Cao, Gedajlovic, & Zhan, 2009). Ambidexterity is shaped by an array of factors related to the structure (e.g., Jansen, Van den Bosch, & Volberda, 2006), leadership characteristics (e.g., Havermans et al, 2015) and broader context (e.g., Gibson & Birkinshaw, 2004).…”
Section: Influence Tactic Ambidexterity and Managers' Task Performancementioning
confidence: 99%
“…Human capital may be defined as the acquired knowledge, skills, and experience of individuals which enable them to act in new ways which are economically valuable to both the individual and to the organization (Call, Nyberg, & Thatcher, 2015;Felício, Couto, & Caiado, 2014;Greve, Benassi, & Sti, 2010;Makela, Bjorkman, & Ehrnrooth, 2009;Nahapiet & Ghoshal, 1998). Human capital brings value to the organization as a standard of competency and creativity that employees possess which allows them to solve problems, create new knowledge, challenge current practices, and identify and leverage performance opportunities (Kang & Snell, 2009;Kostopoulos, Bozionelos, & Syrigos, 2015;Subramaniam & Youndt, 2005).…”
Section: Description Of Conceptsmentioning
confidence: 99%
“…This evolved and complete conceptual definition allows social capital to be applied in a wide range of settings and from the micro level, such as an individual, to the macro level such as an entire population (Grootaert & Van Bastelaer, 2002). social unit with similar backgrounds, status, or experience to each other such as a family, friend, or a colleague (Baughn, Neupert, Anh, & Hang, 2011;Debrulle, Maes, & Sels, 2014;Djuric & Filipovic, 2015;Hofmeyer, 2013;Kostopoulos et al, 2015). These strong network ties assist individuals with access to information and support but may limit the amount of information that is assimilated from outside the social unit.…”
Section: Description Of Conceptsmentioning
confidence: 99%
“…Recently, Kostopoulous, Bozoinelos and Syrigos (2015) reported that organizationallevel high performance human resources (HPHR) practices, which foster a context that provides the unit's workforce with ability, motivation and opportunities to perform and use diverse knowledge assets (p. S115), facilitate complex learning (exploratory and exploitative learning activities). Exploratory learning refers to search, experimentation and discovery of new knowledge, whereas exploitative learning is associated with the refinement, efficient use and implementation of current knowledge and skills.…”
Section: The Moderating Role Of Hr Learning Practicesmentioning
confidence: 99%